Pengaruh Covid-19 Terhadap Produktivitas Bongkar Muat di BUP PT. DABN Cabang Probolinggo - Prasetyo, Alfandi Bagas; Setiono, Beni Agus (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2020)
The port is an important means for sea transportation that makes the distance achieved will feel closer or faster, especially for the developing regional economic sector because the center of goods production can be marketed smoothly. The high productivity of the port shows that the port has provided and is seeking decent service. Corona Virus Disease 2019 or better known as Covid-19 in December 2019, and spread to Indonesia in March 2020. The sea transportation sector received a major impact from the reduction in community activities during the Covid-19 pandemic. The main activities of ports that support world trade must be continue to run safely during the Covid-19 pandemic, which of course requires policies to deal with this situation. The loading and unloading performance can be affected by bad weather and obstacles that have an impact on obstacles, in this case the Covid-19 pandemic is one of the influential factors in developing activities at ports. Research purposes is to determine the effect of the Covid-19 pandemic on the productivity of loading and unloading at BUP PT. DABN Probolinggo branch. Descriptive qualitative research, the approach used in writing this final project is a field research approach. The effect of Covid-19 on loading and unloading productivity at BUP PT. DABN Probolinggo Branch before and during the Covid-19 pandemic, obtaining Covid-19 results only affected the process before the ship docked at the port, namely additional health checks on the crew regarding indications of exposure to the Covid-19 virus. Meanwhile, in terms of loading and unloading productivity, based on data obtained, the difference in the number of shiploads before and during the pandemic there was an increase in the number of 72 ships docked (an increase of 0.11%) and the difference in the number of cargoes increased by 98,260 tons (an increase of 0.062%). Covid-19 only has an impact on additional procedures carried out before the ship docks at the port, namely the port health officer is obliged to check the health of the ship for any indications of the Covid-19 virus on the crew.